2017
DOI: 10.4269/ajtmh.16-0680
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella Infection in Hematophagous, Insectivorous, and Phytophagous Bat Populations of Central Mexico and the Yucatan Peninsula

Abstract: Although emerging nonviral pathogens remain relatively understudied in bat populations, there is an increasing focus on identifying bat-associated bartonellae around the world. Many novel strains have been described from both bats and their arthropod ectoparasites, including, a zoonotic agent of human endocarditis. This cross-sectional study was designed to describe novel strains isolated from bats sampled in Mexico and evaluate factors potentially associated with infection. A total of 238 bats belonging to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 41 publications
(57 reference statements)
1
28
0
Order By: Relevance
“…The overall Bartonella prevalence of (23.95%) among the common vampire bats in the present study was lower than those reported in previous studies conducted in Latin America. Previously, bartonellae prevalence of 37.9% (39/103)–48.4% (15/31) was reported among D. rotundus sampled in Guatemala (Bai et al, ; Wray et al, ), 55.6% (10/18) in Peru (Bai et al, ), and 38% (41/2018) in Mexico (Stuckey, Chomel, et al, ). Among 193 D. rotundus sampled in Peru and Belize, a Bartonella prevalence of 67% was reported (Becker, Bergner, et al, ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The overall Bartonella prevalence of (23.95%) among the common vampire bats in the present study was lower than those reported in previous studies conducted in Latin America. Previously, bartonellae prevalence of 37.9% (39/103)–48.4% (15/31) was reported among D. rotundus sampled in Guatemala (Bai et al, ; Wray et al, ), 55.6% (10/18) in Peru (Bai et al, ), and 38% (41/2018) in Mexico (Stuckey, Chomel, et al, ). Among 193 D. rotundus sampled in Peru and Belize, a Bartonella prevalence of 67% was reported (Becker, Bergner, et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, Bartonella spp. have been detected in vampire bats from Guatemala (Bai et al, ), Peru (Bai et al, ; Becker, Bergner, et al, ; Wray et al, ), Belize (Becker, Bergner, et al, ), and Mexico (Moskaluk et al, ; Stuckey, Chomel, et al, ) in Latin America. Becker, Bergner, et al () highlight the increasing risk of spillover of pathogenic Bartonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…As the gltA gene is not highly transcribed, we also tested sequences for matches to Bartonella DNA-directed RNA polymerase subunit B ( rpoB ). We selected two rpoB sequences (Genbank accessions KY629892 and KY629911) from a study of vampire bat Bartonella [ 16 ] for which the same individuals exhibited 100% identity in the gltA gene to our blood sequences, and we used Bowtie2 to map quality filtered reads and contigs to those sequences [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…Common vampire bats ( Desmodus rotundus ) have high prevalence of Bartonella throughout their large geographic range in Latin America [ 15 , 16 , 24 , 44 ]. Vampire bats are of particular concern because they subsist on blood, which could create opportunities for Bartonella transmission to humans and livestock either from bites during blood feeding or through vector sharing facilitated by close proximity [ 45 – 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Faecal samples were collected from a single roost of vampire bats in Lamanai, Belize. Colon and anal samples were collected from two more populations of vampire bats and the two species of non-haematophagous bats in the Mexican states of Morelos and Veracruz [18]. Faecal samples from vampire finches were collected from the Galapagos islands of Darwin and Wolf during the blood-feeding season, sharpbeaked ground finch samples were collected from the island of Pinta and Genovesa ground finch samples were collected from the island of Genovesa following standardized methods for birds [19].…”
Section: Materials and Methods (A) Sample Collectionmentioning
confidence: 99%